Varipes (Ephemeroptera: Baetidae) in Venezuela: description of a new species - CASTILLO, MARÍA MERCEDES; PÉREZ, BELKYS (Revista Colombiana de Entomología, 2011)
The genus Varipes is reported for the first time for Venezuela. a new species of the genus Varipes is described. Nymphs of V. sancarlos n. sp. were collected in the San Carlos river, Cojedes. The morphology of the nymphs similar to descriptions of other Varipes species. Physical habitat and water quality conditions at the San Carlos River suggest that V. sancarlos can occur in moderately disturbed rivers.